THE EFFECT OF COOPERATIVE LEARNING ON MATHEMATICAL LEARNING OUTCOMES IN TERMS OF LEARNING ACTIVITIES FOR CLASS X STUDENTS OF SMK - Tyas Setyarfi; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Implementing mathematics learning in class X Muhammadiyah Vocational High School (SMK Muhammadiyah) 2 Yogyakarta with a cooperative learning model is less than optimal. Students do activities that are not related to learning activities during the learning activity to disturb learning concentration. This research aims to determine the influence of cooperative learning on the learning outcomes of mathematics in class X students of SMK Muhammadiyah 2 Yogyakarta in the 2017 / 2018 odd semester. This research population is the students of class X Office Administration of SMK Muhammadiyah 2 Yogyakarta, which consisted of two classes. This research sample is taken from the entire population, determining the experiment class of research using random sampling. To get data of research, will use observation methods for learning activity data and test data methods on learning mathematics. Research instrument test: validity test, different power test, and reliability test. Analysis prerequisite tests include the normality test and homogeneity test. Data analysis using two-way variance analysis with unequal cell numbers. The results showed no significant effect of cooperative learning model factors on students' mathematics learning outcomes. This can be seen in the calculation with a significant level of 5%, dk: =1 dan = 58, . There is a significant influence on learning activity factors on students' mathematics learning outcomes. This can be seen from the calculation results at a significant level of 5%, dk: =1 dan =58 we can get . There is no significant interaction between cooperative learning models and learning activities on students' mathematics learning outcomes. This can be seen from the calculation results at a significant level of 5%, dk: =1 dan =58 so that , so the third hypothesis has been tasted by rejecting